Peran PAK Gereja terhadap Fenomena Toxic Masculinity pada Kalangan Laki-laki di Era Teknologi Digital - Aritonang, Delinda Elizabeth; L. Tobing, Fernando Dapot Hamonangan (Institut Agama Kristen Negeri Manado, 2024)
This research aims to show that toxic masculinity is a phenomenon that often occurs in men in the era of digital technology. Men are considered human beings who must be strong, tough, not cry easily and must not express emotions. However, in reality, men who do not behave like that will immediately be stigmatized by society and find it difficult to accept it. This article was written using a qualitative research method with a descriptive approach. Descriptive qualitative methods are used to collect data, analyze and evaluate through critical thinking from books, journal articles and the Bible related to the discussion. This method divides this research into three important points. First, the phenomenon of toxic masculinity among teenagers. Second, the Church's Christian religious education in the era of digital technology. Third, the role of church Christian religious education in the phenomenon of toxic masculinity among the younger generation in the era of digital technology. The results of this research are the value of respect for men related to toxic masculinity so that they are brave and free to express their emotions as well as the role of Christian Religious Education in church life to break the stigma about toxic masculinity. The conclusion is to convey a message about the role of Christian religious education by increasing good perspectives within the church regarding toxic masculinity.